Analisis Framing Gerakan Sosial: Studi Pada Gerakan Aksi Bela Islam 212 - Riadi, Bagus; Drajat, Diki (LP2M IAIN Syekh Nurjati Cirebon, 2019)
The 212 Movement was once a lively issue being discussed among academics. Each academician has his own perspective in terms of analysis of the emergence of the Islamic Defending Action. One of the highlights of an analysis from Vedi Hadiz which explains that the phenomenon of Islamic Defending Action is actually a formof disillusionment with the failure of the international system. Those who are marginalized then use the vehicle